Dehydration of fructose to obtain hydroxymethylfurfural - Garrido Schaeffer, A. (2012)
The objective of this work is the transformation of fructose to 4-hydroxymethylfurfural by a dehydratation process using the 4-toluenesulfonic acid as catalyst . The reaction was carried out using solutions of fructose in water and fructose in water-acetone (50% volume) in a batch reactor at temperatures of 372 K and 348 K respectively. The yield reached a maximum of 16% to hydroxymethylfurfural, an intermediate for obtaining fuel furan.